On absence and abundance: biography as method in archival research. Issue 4 (1st March 2017) - Hodder, Jake
Abstract : Geographical scholarship has rightly problematised the act of archival research, showing how the practice of archiving is not only concerned with how a society collectively remembers, but also forgets. As such, the dominant motif for discussing historical methods in geography has been through the lens of absence: the archive is a space of 'traces', 'fragments' and 'ghosts'. In this paper I suggest that the focus on incompleteness and partiality, while true, may also belie what many geographers working in archives find their greatest difficulty: an overwhelming volume of source materials. I reflect on my own research experiences in the pacifist archive to suggest that the growing scale and scope of many collections, along with the taxing research demands of transnational perspectives, pose immediate practical challenges for geographers characterised as much by abundance as by absence. In the second half of the paper, drawing on recent scholarship in history and geography, I argue that the method of biography offers one possible strategy for navigating archival abundance, allowing geographers to tell stories that are wider, deeper and more revealingly complex within the existing time and financial constraints of humanities research.